The Dynamics of Interdependence between Sharia Assets (ISSI, SUKUK) and the Macroeconomic System in Indonesia - Ismail Ismail; A Syathir Sofyan (Best Journal of Administration and Management, 2026)
This study aims to analyze the dynamics of interdependence between sharia assets, namely the Indonesian Sharia Stock Index (ISSI) and sukuk, with Indonesian macroeconomic variables using the Vector Autoregression (VAR) approach. The macroeconomic variables analyzed include the BI exchange rate, BI Rate, inflation, export value, money supply (M2), gold price, West Texas Intermediate (WTI) crude oil price, and the Industrial Production Index (IPI). The data used is a monthly time series for the period July 2011–December 2024 with a sample of 160 observations. The results of the stability test indicate that the VAR(1) model used is stable and suitable for further analysis. The Granger causality test indicates that most variables do not have a significant causal relationship, except for the exchange rate (KURS) which is proven to affect almost all other variables. The Impulse Response Function (IRF) test shows that most shocks to the ISSI, inflation, M2, gold, and WTI variables do not generate significant responses to other variables, while sukuk shows a positive response to shocks from the BI Rate, KURS, and IPI in the short term These findings emphasize the importance of strengthening Islamic financial instruments and exchange rate stability in supporting the integration of Islamic financial markets with the national macroeconomic system.